Prognostic Value of PSMB5 and Correlations with LC3II and Reactive Oxygen Species Levels in the Bone Marrow Mononuclear Cells of Bortezomib-Resistant Multiple Myeloma Patients - Eva Plakoula; Georgios Kalampounias; Spyridon Alexis; Evgenia Verigou; Alexandra Kourakli; Kalliopi Zafeiropoulou; Argiris Symeonidis (Current Issues in Molecular Biology)
Proteasome inhibitors (PIs) constitute the most common type of induction treatment for multiple myeloma. Interactions between the proteasome, autophagy, and reactive oxygen species (ROS) have been shown in the past, thus emphasizing the need for a better understanding of the underlying pathophysiology. For this study, bone marrow mononuclear cells from 110 myeloma patients were collected at different disease stages. PSMB5 and LC3I/II protein levels were determined using Western blot, proteasome proteolytic activity (PPA) with spectrofluorometry, and ROS with flow cytometry. PSMB5 accumulation was found to diminish after PI treatment (p-value = 0.014), and the same pattern was observed in PPA (p-value < 0.001). Conversely, LC3II protein levels were elevated at both remission and relapse compared to baseline levels (p-value = 0.041). Patients with a baseline PSMB5 accumulation lower than 1.06 units had longer disease-free survival compared to those with values above 1.06 units (12.0 ± 6.7 vs. 36 ± 12.1 months; p-value < 0.001). Median ROS levels in plasma cells were significantly higher at relapse compared to both baseline and remission levels (p-value < 0.001), implying poor prognosis. Overall, post-treatment PSMB5 reduction could indicate a shift from proteasomal to autophagic degradation as a main proteostatic mechanism, thus explaining resistance. The elevated oxidative stress in PI-treated patients could possibly serve as an additional compensatory mechanism.